2011
DOI: 10.1016/j.neulet.2009.06.079
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in CA1 hippocampal neurons of the UBE3A deficient mouse model for Angelman syndrome

Abstract: Angelman syndrome (AS) is a severe neurological disorder caused by a deficiency of ubiquitin protein ligase E3A (Ube3a), but the pathophysiology of the disease remains unknown. We now report that in the brains of AS mice in which the maternal Ube3a allele is mutated (m-) and the paternal allele is potentially inactivated by imprinting (p+) (Ube3a m-\p+) the mitochondria are abnormal and exhibit a partial oxidative phosphorylation (OXPHOS) defect. Electron microscopy of the hippocampal region of the Ube3a m-\p+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 28 publications
5
55
2
Order By: Relevance
“…In AS mouse models, the deficiency of Ube3a protein causes a reduction of dendrites spine density and dendritic length in multiple brain areas including hippocampus, cortex layer Ⅲ-Ⅴ and cerebellum [19,20] AS mice also show defects of dendrite polarization of pyramidal neurons in cortex and hippocampus, decreased dendritic arborization in cortex [21] and decreased synaptic vesicle density in hippocampus [22]. These morphological changes are consistent with the observed functional deficits.…”
Section: Genetic Abnormality and Phenotypic Presentationsupporting
confidence: 59%
See 1 more Smart Citation
“…In AS mouse models, the deficiency of Ube3a protein causes a reduction of dendrites spine density and dendritic length in multiple brain areas including hippocampus, cortex layer Ⅲ-Ⅴ and cerebellum [19,20] AS mice also show defects of dendrite polarization of pyramidal neurons in cortex and hippocampus, decreased dendritic arborization in cortex [21] and decreased synaptic vesicle density in hippocampus [22]. These morphological changes are consistent with the observed functional deficits.…”
Section: Genetic Abnormality and Phenotypic Presentationsupporting
confidence: 59%
“…The loss of neurons may be due to either impaired metabolism or the disturbance of genes involved in cell death process [49], or both. It was also shown that mitochondria in AS mouse exhibited a smaller size in the hippocampus and a partial oxidative phosphorylation defect in the whole brain [22]. Another study revealed that proliferation of neurons was disrupted in AS mice due to the increased expression of cyclin-dependent kinase inhibitor p27, whose degradation is mediated by the Ube3a [50].…”
Section: Pathophysiological and Molecular Changesmentioning
confidence: 99%
“…Similar to the observation of small brain size in human samples from Angelman’s syndrome, the total brain weight, as well as the weight of the cortex and cerebellum, is lower in a mouse model with maternal Ube3a deleted ( Ube3a m−/p+ ) [181]. Also, the density of presynaptic vesicles, as well as spine density and length, in hippocampal CA1 neurons is lower compared to WT controls [342]. In the visual cortex of Ube3a m−/p+ mice, cortical thickness and cell density in layers II, III and V are unaffected [312], cell density of inhibitory interneurons is unaffected in layers II and III [368], spine density is decreased in layer V after 21 days of age [86, 196, 312], maintenance of spine density after sensory stimulation is deficient [196, 394], with more thin spines and fewer stubby spines in the disease model than in the WT [196] and presynaptic GABA vesicle density is decreased at both inhibitory and excitatory synapses [368].…”
Section: Lessons From Animal Modelsmentioning
confidence: 72%
“…Defects in fluid consumption and licking observed in the mouse model (Heck et al, 2008) may recapitulate the swallowing problems and excessive drooling frequently associated with AS individuals (Williams et al, 2006). Mitochondrial dysfunction in CA1 hippocampal neurons (Su et al, 2009) and impaired adult neurogenesis (Mardirossian et al, 2009) are also observed in the mouse AS models.…”
Section: Animal Models Of Angelman Syndromementioning
confidence: 90%